Introduction to electron microscopy for biologists - Allen, Terence D. (Amsterdam, Netherlands Elsevier/Academic Press, 2008)
This volume demonstrates how cellular and associated electron microscopy contributes to knowledge about biological structural information, primarily at the nanometer level. It presents how EM approaches complement both conventional structural biology (at the high end, angstrom level of resolution) and digital light microscopy (at the low end, 100-200 nanometers).--Provided by publisher.
High pressure freezing and freeze substitution of Schizosaccharomyces pombe and Saccharomyces cerevisiae for TEM / S. Murray -- Electron probe X-ray microanalysis for the study of cell physiology / E. Fernandez-Segura and A. Warley -- Preparation of cells and tissues for immuno EM / P. Webster, H. Schwarz and G. Griffiths -- Quantification of structures and gold labeling in transmission electron microscopy / J. Lucocq -- Combined video fluorescence and 3D electron microscopy / A.A. Mironov, R.S. Polishchuk and G.V. Beznoussenko -- From live-cell imaging to scanning electron microscopy (SEM): the use of green fluorescent protein (GFP) as a common label / S.P. Drummond and T.D. Allen -- Immunolabeling for scanning electron microscopy (SEM) and field emission SEM / M.W. Goldberg -- Immunogold labeling of thawed cryosections / P.J. Peters and J. Pierson -- Close-to-native ultrastructural preservation by high pressure freezing / D. Vanhecke, W. Graber and D. Studer -- High-pressure freezing and low-temperature fixation of cell monolayers grown on sapphire coverslips / S. Reipert and G. Wiche -- Freeze-fracture cytochemistry in cell biology / N.J. Severs and H. Robenek -- Three-dimensional molecular architecture of the plasma-membrane-associated cytoskeleton as reconstructed by freeze-etch electron tomography / N. Morone ... [et al.] -- Visualization of dynamins / J.A. Mears and J.E. Hinshaw -- Correlated light and electron microscopy of the cytoskeleton / S. Auinger and J.V. Small -- Electron microscopy of intermediate filaments: teaming up with atomic force and confocal laser scanning microscopy / L. Kreplak ... [et al.] -- Studying microtubules by electron microscopy / C. Moores -- Electron microscopy of collagen fibril structure in vitro and in vivo including three-dimensional reconstruction / T. Starborg ... [et al.] -- Visualization of desmosomes in the electron microscope / A. Scothern and D. Garrod -- A protocol for isolation and visualization of yeast nuclei by scanning electron microscopy / S. Murray and E. Kiseleva -- Scanning electron microscopy of nuclear structure / T.D. Allen ... [et al.] -- Electron microscopy of lamin and the nuclear lamina in Caenorhabditis elegans / M. Cohen ... [et al.] -- Visualization of nuclear organization by ultrastructural cytochemistry / M. Biggiogera and S. Fakan -- Scanning electron microscopy of chromosomes / G. Wanner and E. Schroeder-Reiter -- Infection at the cellular level / C. Goosmann, U.A. Abed and V. Brinkmann -- Electron microscopy of viruses and virus-cell interactions / P. Wild.
Includes bibliographical references and index.
Keywords: Electron microscopy -- Technique; Cytology -- Technique; Microscopy, Electron -- Methods; Cytological techniques; Electronic book